METHODS OF DETERMINATION OF POTENTIAL AREAS OF FORMING SOCIO-ECONOMIC INNOVATIVE CLUSTERS IN THE REGION - Oleg A. Donichev; Olga G. Molchanova (Статистика и экономика, 2016)
The article describes the main problems of formation of innovation clusters in the regions, the role and the importance of government in these issues. The characteristics of the main socio-economic and innovative performances of the region are analyzed to determine its potential for creating innovative economic cluster. The methods for detecting possible potential areas of formation of such cluster are developed.